Unsuccessful treatment outcome and associated risk factors. A prospective study of DR-TB patients from a high burden country, Pakistan - Massud, Asif; Khan, Amer Hayat; Syed Azhar, Syed Sulaiman; Ahmad, Nafees; Shafqat, Muhammad; Long, Chiau Ming * (PLOS, 2023)
Introduction: Tuberculosis (TB), a curable and preventable infectious disease, becomes difficult to treat if resistance against most effective and tolerable first line anti-TB drugs is developed. The objective of the present study was to evaluate the treatment outcomes and predictors of poor outcomes among drug-resistant tuberculosis (DR-TB) patients treated at a programmatic management unit of drug resistant tuberculosis (PMDT) unit, Punjab, Pakistan.